2018
DOI: 10.31925/farmacia.2018.6.24
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Evaluation on the Consumption of Antibiotics in Community Pharmacies

Abstract: According to the statistics, each year 400,000 Europeans develop infections with antibiotic-resistant bacterial strain, and 25,000 die due to the exhaustion of all therapeutic resources. These statistics are alarming, considering that medical services have become lately more and more accessible, but the "antibiotics era", namely the prescribing of these pharmacological agents on a large scale, generated the present situation. There is a category of patients who seek specialist medical services, yet many of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Rats were obtained from animal house of Faculty of Veterinary Medicine (University of Zabol, Iran) and were maintained in normal laboratory conditions (22 ± 2 °C, 20% humidity, 12 h:12 h light-dark cycle) [33]. The light intensity of the animal house was 300 lx and the rats were housed individually in polycarbonate open-top cages [34]. After 2 weeks of acclimatization, the rats were randomly divided in four groups.…”
Section: Animal Groupingmentioning
confidence: 99%
“…Rats were obtained from animal house of Faculty of Veterinary Medicine (University of Zabol, Iran) and were maintained in normal laboratory conditions (22 ± 2 °C, 20% humidity, 12 h:12 h light-dark cycle) [33]. The light intensity of the animal house was 300 lx and the rats were housed individually in polycarbonate open-top cages [34]. After 2 weeks of acclimatization, the rats were randomly divided in four groups.…”
Section: Animal Groupingmentioning
confidence: 99%
“…The evolution of Rx products at a national level In Romania, there is a policy of price control just for prescription-only medicines [12,14,20]. The comparable situation (July 2018 -June 2019) of drug consumption after 4 years since the adoption of the price regulation for Rx products is found in Table II.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, large variations have been reported in the extent of noncompliance in individual patients and large populations. Previous regional medication adherence research revealed the importance of therapeutic patient education for patient compliance in North-Western Romania [15]. The use of antithrombotic agents is recommended in order to reduce the rates of morbidity and mortality in patients with ACS.…”
Section: Descriptive Analysis Of Bleeding Rates By Patterns Of Drug Usementioning
confidence: 99%